GUT and Flavor Models for Neutrino Masses and Mixing - Meloni, Davide (Frontiers in Physics, 2017)
In the recent years experiments have established the existence of neutrino oscillations and most of the oscillation parameters have been measured with a good accuracy. However, in spite of many interesting ideas, no real illumination was sparked on the problem of flavor in the lepton sector. In this review, we discuss the state of the art of models for neutrino masses and mixings formulated in the context of flavor symmetries, with particular emphasis on the role played by grand unified gauge groups.